2019
DOI: 10.1130/gsatg393a.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Introductory Geoscience Courses in Preparing Teachers—And All Students— For the Future: Are We Making the Grade?

Abstract: Introductory geoscience courses enroll hundreds of thousands of students a year, most of whom do not major in the geosciences. For many, including future K-12 teachers, an introductory course is the only place they will encounter Earth science at the college level. New standards for K-12 science education have profound implications for teacher preparation, particularly in Earth science. The new standards call for taking a systems approach, highlighting how humans interact with Earth, making use of science and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Introductory courses reach a large proportion of the students taking geoscience courses. The number of students enrolled in the introductory courses represented in the survey responses was calculated from numbers entered by respondents and totaled 70,198 for the 2016 survey, or approximately 20% to 25% of students enrolled in geoscience courses (Egger, 2019). Given the large number of students in introductory geoscience courses, and the demonstrated value of career information to attracting students to the sciences (Hoisch & Bowie, 2010), introductory courses may be a key place to provide information and support to students related to geoscience careers.…”
Section: Course Typementioning
confidence: 99%
“…Introductory courses reach a large proportion of the students taking geoscience courses. The number of students enrolled in the introductory courses represented in the survey responses was calculated from numbers entered by respondents and totaled 70,198 for the 2016 survey, or approximately 20% to 25% of students enrolled in geoscience courses (Egger, 2019). Given the large number of students in introductory geoscience courses, and the demonstrated value of career information to attracting students to the sciences (Hoisch & Bowie, 2010), introductory courses may be a key place to provide information and support to students related to geoscience careers.…”
Section: Course Typementioning
confidence: 99%
“…Given that teachers have a key role in improving students' learning in ES, well-designed courses for professional development should be highly prioritized (Van der Flier-Keller et al, 2011). Many teachers in training receive their only ES education at a primary college-level, and therefore the introductory courses play a critical role of preparing future teachers (Egger, 2019). Egger's (2019) research indicated that although ES education has been moving to more active and student-centered teaching strategies, (e.g.…”
Section: Pedagogical Differencementioning
confidence: 99%
“…Many teachers in training receive their only ES education at a primary college-level, and therefore the introductory courses play a critical role of preparing future teachers (Egger, 2019). Egger's (2019) research indicated that although ES education has been moving to more active and student-centered teaching strategies, (e.g. the proportion of traditional lecturing has decreased over the years with a parallel increase in active learning strategies such as discussions and activities), more effort is required to further improve learning as the following problems remain: 1) the concept of systems thinking is rarely mentioned and incorporated in introductory ES courses; 2) little time is spent on highlighting human connections with Earth's systems; and 3) engaging with data and practices is relatively rare compared to emphasis on content knowledge.…”
Section: Pedagogical Differencementioning
confidence: 99%
See 2 more Smart Citations